Preparation of Carbon-Coated TiO2 Immobilized on Expanded Graphite/Activated Carbon Composite and its Application for Photodegradation of Formaldehyde Gas - Liu, Chengbao; Qian, Junchao; Gu, Cheng; Chen, Zhigang; Chen, Feng; Xu, Zheng; Li, Ping; He, Fengjuan; Wu, Zhenying (Asian Journal of Chemistry, 2014)
A new material carbon-coated TiO2 immobilized on expanded graphite/activated carbon composite (C-TiO2/EGCs) was synthesized to solve indoor air pollution problems. The TiO2 coated by carbon layer was immobilized on the outer surface of expanded graphite-based carbon/ carbon composites EGCs. The porous texture and the microstructure of the composite were analyzed by using nitrogen adsorption-desorption measurements, XRD, SEM and TEM. The influence of conditions on the formaldehyde degradation was investigated. The results indicated that carbon film not only ensured the adsorption performance and realize dv higher photocatalytic degradation ability of formaldehyde.